The Influence of Educational Videos in Increasing First Aid Knowledge and Skills in Village Communities - Kusumaningrum, Bintari Ratih; Suryanto, Suryanto; Fathoni, Mukhammad; Riwayanto, Firmananda Dwi; Karmawan, Limas Madjid; Nursuhaida, Haffa Syafana; Handayani, Auliya; Ayu, Lintang Ilal; Wulansari, Eny (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Education about first aid of accident in communities is important. Currently, technology for education has developed. It is not only through books or leaflets, but video is a more interesting medium for public education. Purpose. The aim of this study was to determine the effect of educational videos on first aid knowledge and skills for home injury in the village community. Methods We used quasi experimental research design with 59 samples obtained by purposive sampling divided into 2 groups, namely control (n=30) and intervention(n=29). The intervention group was given education using video, while the control group received education using booklet. Before the intervention, a pre-test was carried out, then the video and booklet were given to respondents to read and view,  after one week the post-test was measured again. The variables studied are first aid knowledge and skills. The instrument used is a questionnaire about first knowledge and skills which is filled in by the community. Data analysis used paired t test and independent t test. Result. The results show there was a significant increase in knowledge scores in the control group (p value = 0.009), but there was no significant increase in the intervention group (p value 0.677). Meanwhile, in the skills variable, there was a significant increase in scores in the control group (p value 0.001) and in the intervention group (0.024). Between two groups measurements, they did not differ significantly between the knowledge of the control group and the intervention group (p value of knowledge 0.162; p value of skills 0.360). Even though there is no difference between the control and intervention groups, both educational methods can increase the knowledge and skills of village communities in providing home injury first aid. Conclusion In conclusion,  educational videos themselves do not have a significant impact on first aid knowledge. This must be combined with modules and assistance from health workers to provide education.